Coherent changes in wood charcoals, site occupation and lithic technology across the MIS 4/3 transition at Klein Kliphuis rock shelter, South Africa. (10th July 2022) - Mackay, Alex; Cartwright, Caroline R.
Abstract: We explore the correspondence between changing palaeoenvironments, patterns of site use, and lithic technology at the rock shelter site Klein Kliphuis (South Africa) across the interval 65–55 000 years before present. This period coincides with the termination of Marine Isotope Stage (MIS) 4, and the disappearance of an iconic late Pleistocene archaeological unit known as the Howiesons Poort. Wood charcoals indicate sufficient soil moisture around Klein Kliphuis throughout the Howiesons Poort to support diverse tree species at a time when site occupation was relatively intense. At least some fuelwood‐gathering in this period may have been undertaken to support heat treatment of silcrete, which was the dominant lithology in tool production. A coherent set of changes occurs across the MIS 4/3 transition: occupational intensity declines, tracked by declining diversity of fuelwood species, an increase in the proportion of charcoals from shrubs and small flowering plants, lower prevalence of silcrete, and less heat treatment. While declining soil moisture is implied, there appears to be a significant change in behaviour relating to site usage, whereby foraging for dense fuelwoods was replaced by the construction of 'fast fires' that may reflect briefer visits and increased forager mobility in early MIS 3.